Management of tibial plateau fractures with compromised soft tissue using hybrid external fixator - Sharma, Mahesh K.; Jain, Mukul; Jain, Harish K.; Khichar, Sukhveer; Jadoo, Rahul (International Journal of Research in Orthopaedics, 2020)
Tibial plateau fractures with high energy trauma are complex injury due to its precarious soft tissue envelope. High energy trauma has high incidence of open fractures, articular depression, fracture comminution and displacement, soft tissue injury, and neurovascular compression. It is often difficult to achieve and maintain reduction and commonly predisposes to secondary arthritis. Hybrid external fixator minimizes the iatrogenic soft tissue damage, provides adequate fixation of the fracture, permits early range of motion, easy wound care and leave no large implant in subcutaneous position. This study was performed to evaluate the functional and radiological outcome with this procedure. In this case series, prospective study of 15 cases of tibial plateau fractures were treated with hybrid external fixator at tertiary care teaching hospital in southern Rajasthan from July 2018 to June 2019. The functional and radiological outcome was assessed by Rasmussen functional and radiological score. The mean interval between surgery and union was 16 weeks (range 13 to 18 weeks). Rasmussen functional results were acceptable in 13 cases (86.66%) comprising excellent in 9 (60%), good in 4 (26.66%), and fair in 2 (13.33%). Rasmussen radiological results were acceptable in 13 cases (86.66%) comprising excellent in 9 (60%), good in 4 (26.66%), and fair in 2 (13.33%). Minimal internal and hybrid external fixation for management of tibial plateau fracture with compromised soft tissue is more biological, require less surgical time, less hospital stay, very effective in compromised soft tissue, highly cost effective and has minimal complications with good functional outcome.